Fighting Cancer Stem Cell Fate by Targeting LIS1 a WD40 Repeat Protein - Brehar, Felix M.; Dragomir, Mihnea P.; Petrescu, George E. D.; Gorgan, Radu M. (Frontiers in Oncology, 2019)
Cancer is one of the most frequent and devastating diseases. Previous reports have shown that radio and chemo-resistant cancer stem cell (CSC) population is primarily responsible for cancer recurrences after radiotherapy and chemotherapy. Other studies demonstrated that Lissencephaly-1 (Lis1) protein, also known as platelet activating factor acetylhydrolase 1b regulatory subunit 1 (Pafah1b1), a dynein-binding protein involved in neural stem cell division, plays a crucial role in maintaining CSC population in hematological malignancies. Moreover, one recent report demonstrated that Lis1 gene is preferentially expressed in CD133+ glioblastoma cells and may have also an important role in regulating CD133+ CSC in glioblastoma. The hypothesis of this paper is that Lis1 plays a key role in maintaining CD133+ CSC population in various solid cancers by controlling the stem cell fate regulatory mechanism. As CD133+ CSC population is responsible for radio- and chemo resistance, which finally determines the cancer recurrences and metastases, identifying the molecular mechanisms which regulate the CD133+ CSC population represents a major target for cancer research. Given the structure of Lis1, which contains WD40 repeat domain, small peptide inhibitors could be used to alter its function. Therefore, the impact of confirming this hypothesis is significant because Lis1 may become an important molecular target for future adjuvant anticancer therapies directed against radio- and chemo resistant CSC population.